Uso de web scraping para mineração de produtos e preços em e-commerce - Oliveira, Wendel Lima (2023)
The`development`of`information`and`communication`technologies`has`led`to`the`emergence`of`collaborative`systems,`such`as`crowdsourcing,`which`allows`the`mutual`sharing`of`data,`as`diverse`as`possible,`generated`by`smartphones`of`a`community`of`users.`One`of`these`most`popular`systems`is`Waze`which`allows`you`to`identify`congestion-free`transit`routes`using`geolocation`information`from`mobile`devices.`LudiiPrice`is`a`crowdsourcing`application`that`is`being`developed`at`UFS`under`the`coordination`of`the`supervisors`of`this`monograph`and`consists`of`a`price`fnder`for`personal`consumables`and`groceries`obtained`by`QR`code`photographed`by`smartphones.`Invoice`data`is`stored`in`a`database`that`is`used`to`respond`to`user`queries.`The`objective`of`this`work`is`to`automatically`populate`this`database`using`a`web`crawler`to`extract`price`data`from`products`published`in`e-commerce`portals.`The`data`obtained`is`processed`using`Natural`Language`Processing`techniques`and`aims`to`suggest`each`item`entered`through`the`invoice.`The`crawler`and`the`suggestions`are`requested`through`an`API,`which`was`built`using`the`Django`framework`that`uses`Python`as`its`language.`As`a`result`of`the`work,`crawlers`are`performed`in`three`e-commerce`that`populate`a`base`and`suggest`items`extracted`from`crawler`for`each`product`present`in`the`invoice`inserted`in`the`LudiiPrice`application.